Regional schools: from projects to hopes - Kapustin, Petr (project baikal, 2020)
The category of schools has recently become one of the most attractive. It may be due to its paradoxical features: it contains both the tunes of tradition and rootedness and the pretensions to capture certain areas of the future – already under its own inertia and the would-be power of the historical trend. However, today’s “schools” have nothing natural; their current configurations remain in force for quite a long time because they were designed and rather skillfully introduced into the well-known present trends. Unfortunately, changes in trends occur too quickly to leave special resources for ideas that are focused on traditions and values of existence and are in highest demand in contemporary architecture. These twists of time and place are discussed in the given article based on the studies of conceptual foundations for the architectural school of the Central Black Earth Region.
Keywords: regional architecture school; content of architectural education; organi ational form of architectural education; region; regional studies; architectural design